The Impact of Trauma-Informed Care on Mental Health Outcomes for Incarcerated Youth: A Longitudinal Study in Bandung, Indonesia - Dedi Affandi; Ericca Dominique Perez; Winata Putri; Anies Fatmawati; Alex Putra Pratama (Scientia Psychiatrica, 2025)
Introduction: Incarcerated youth represent a vulnerable population with disproportionately high rates of trauma exposure and mental health disorders. This study investigated the longitudinal impact of a trauma-informed care (TIC) program on mental health outcomes for incarcerated youth in Bandung, Indonesia. Methods: A quasi-experimental design was employed, comparing a group of incarcerated youth who received TIC with a control group receiving standard care. Participants (n=200) were assessed at baseline, 6 months, and 12 months using validated instruments measuring PTSD symptoms, depression, anxiety, and behavioral problems. Data analysis included repeated measures ANOVA and correlational analyses. Results: Youth in the TIC group demonstrated significant reductions in PTSD symptoms, depression, and anxiety over time compared to the control group. Improvements in behavioral problems were also observed in the TIC group. These positive changes were sustained over the 12-month period. Conclusion: This study provides evidence for the effectiveness of TIC in improving mental health outcomes for incarcerated youth. Implementing TIC programs in juvenile detention facilities is crucial for addressing the mental health needs of this vulnerable population.